THE IMPLEMENTATION OF MAJLIS SULH IN SHARIAH JUDICIAL SYSTEM: A CASE STUDY IN SELANGOR (International Seminar on Syariah and Law (INSLA), 2024)
Sulh serves as a primary out-of-court dispute resolution mechanism designed to settle matrimonial conflicts without resorting to adversarial litigation. As a core component of Alternative Dispute Resolution (ADR) under Islamic Family Law, the effective implementation of sulh has significantly contributed to mitigating court backlogs, notably addressing the 2,736 unresolved cases recorded in the Shariah Court from 2020 until September 30, 2021, while simultaneously reducing the judicial workload. This study outlines three primary objectives: first, to identify the conceptual foundations of sulh from an Islamic perspective; second, to examine its operational implementation within the state of Selangor; and third, to propose strategic recommendations positioning sulh as a premier mechanism to alleviate systemic case backlogs. Employing a qualitative research methodology, this study utilizes a case study design, extensive literature review of journals and textbooks, and semi-structured interviews with key judicial informants within the Selangor Shariah Court framework. The findings indicate that while the implementation of sulh in Selangor aligns closely with Islamic jurisprudential principles, its execution faces distinct institutional and operational challenges that must be addressed to maximize its efficacy.